2017
DOI: 10.1016/j.jpeds.2016.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Exposure in the Neonatal Intensive Care Unit: Room Type and Other Predictors

Abstract: Objective To quantify early auditory exposures in the neonatal intensive care unit (NICU) and evaluate how these are related to medical and environmental factors. We hypothesized that there would be less auditory exposure in the NICU private room, compared with the open ward. Study design Preterm infants born at ≤ 28 weeks gestation (33 in the open ward, 25 in private rooms) had auditory exposure quantified at birth, 30 and 34 weeks postmenstrual age (PMA), and term equivalent age using the Language Environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
92
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 33 publications
5
92
1
4
Order By: Relevance
“…The study by Chow and Shellhaas [22] was the only one recruiting and measuring infants of all gestational ages (mean 34 ± 5.1 weeks; the age range was not reported). Accordingly, the mean birthweight in the study by Chow and Shellhaas [22] (2,410 ± 1,070 g) was much higher than that in the studies by Caskey et al [23] (896 ± 195 g) and Pineda et al [37] (855 ± 184 g). The Language Environment Analysis (LENA) digital language processor (LENA Foundation, Boulder, CO, USA) was used in all studies, with a 16-h recording time.…”
Section: Observational Studies Of Measured Language Exposurementioning
confidence: 51%
See 4 more Smart Citations
“…The study by Chow and Shellhaas [22] was the only one recruiting and measuring infants of all gestational ages (mean 34 ± 5.1 weeks; the age range was not reported). Accordingly, the mean birthweight in the study by Chow and Shellhaas [22] (2,410 ± 1,070 g) was much higher than that in the studies by Caskey et al [23] (896 ± 195 g) and Pineda et al [37] (855 ± 184 g). The Language Environment Analysis (LENA) digital language processor (LENA Foundation, Boulder, CO, USA) was used in all studies, with a 16-h recording time.…”
Section: Observational Studies Of Measured Language Exposurementioning
confidence: 51%
“…That by Caskey et al [23] was the only study to be given a strong quality rating, whereas those by Pineda et al [37] and Chow and Shellhaas [22] were rated weak. Statistical analysis and reporting were well documented in Caskey et al [23] and Pineda et al [37], but Chow and Shellhaas [22] reported some outcomes in median values and others in mean values, making overall comparisons difficult.…”
Section: Observational Studies Of Measured Language Exposurementioning
confidence: 99%
See 3 more Smart Citations